A comparative study of two intrastromal corneal ring segment models in keratoconus: A retrospective study - Dal, Ali; Erdag, Murat; Canleblebici, Mehmet (Wolters Kluwer Medknow Publications, 2025)
Purpose:This study aimed to assess BioRing's (Biotech, India) clinical and topographic efficacy in treating moderate-to-advanced keratoconus and compare its visual, refractive, and keratometric results to Keraring (Mediphacos, Brazil) at different stages of the disease.Methods:This retrospective study evaluated the results of 74 eyes (58 patients) that received femtosecond laser-assisted intrastromal corneal ring segment implantation from March 2019 to March 2024. The Amsler-Krumeich classification classified the patients as having either moderate or advanced keratoconus. Group 1 comprised 39 eyes with BioRing implants, whereas group 2 consisted of 35 eyes with Keraring implants. We classified each group into moderate and advanced keratoconus categories. Preoperative and 6-month postoperative assessments encompassed uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), refractive errors, and corneal tomography metrics.Results:Both BioRing and Keraring showed statistically significant increases in visual acuity, refractive errors, and topographic parameters between preoperative and postoperative examinations. However, when postoperative results were compared between groups, no significant difference in UCVA was found (P = 0.097). In contrast, the Keraring group had considerably superior BCVA than the BioRing group (P = 0.042). In terms of topographic metrics, Keraring considerably improved keratometric flattening, including Kmax (P = 0.040), K1 (P = 0.012), and K2 (P = 0.024). Subgroup analysis revealed comparable improvements in moderate keratoconus, while Keraring showed superior outcomes in advanced cases.Conclusion:BioRing and Keraring effectively improved visual acuity, refractive errors, and topographic parameters in moderate-to-advanced keratoconus. Keraring showed superior outcomes, particularly in advanced keratoconus.
Keywords: BioRing; intrastromal corneal ring segments; Keraring; keratoconus